On the use of participatory methodologies for video game research: Exploring disaster risk reduction in video games. Issue 3 (October 2019) - Gampell, Anthony Viennaminovich; Gaillard, JC; Parsons, Meg
Video game scholars examining the shortcomings of previous video game research reference the need for new and innovative methodologies. Existing video game research seemingly inhibits organic learning experiences by setting specific research targets or providing players with gameplay instructions, hence utilising methodological approaches that study the learning process from the outside. With the increasing popularity of both serious and mainstream disaster video games, a necessity exists for innovative research to explore how video games can be used as learning tools. Based upon the researchers' own enquiry, this article demonstrates the potential use, benefits and challenges of participatory methodologies for the conduct of video game research. This article pushes back upon traditional video game research methods, reviewing the methodological approaches of existing video game literature and demonstrates how participatory methodologies are currently being used for disaster video game research. An examination of participatory methodologies, being used in disaster video game research, reviews the strengths and challenges of each research approach. Rationalising the potential of participatory methodologies, in the context of constructivist learning theory and active participation, to foster the learning process and explore learning from the inside. As such this article provides an innovative methodological framework, which can be used as a template when considering future video game research.